THE ROLE OF INTRAUTERINE CONTRACEPTION IN THE DEVELOPMENT OF CERVICAL PATHOLOGY - Atakhodzhayeva, F.A.; Kayumova, D.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This article studies the correlation between the prolonged use of intrauterine contraceptive devices (IUDs) and the development of cervical pathology. A comparative analysis of clinical, cytological, colposcopic, and microbiological data was conducted in 74 women with and without IUDs. A higher incidence of inflammatory changes and low-grade cervical intraepithelial neoplasia (CIN 1) was revealed among IUD users.